Studies on Antileutinizing Activity of Melissia Officinalis - Sabir, Dlawer M. (Sulaimani Journal for Pure and Applied Sciences, 2004)
The active Principle responsible for the antihormonal activity of M. officinalis is formed from phenolic precursors. For its formation, an oxidation step was found to be essential. As a test model, an isolated mous leydig cells were used for LH-induced testoserror realease. The freeze-dried extract (FDE) of the plant leaves showed an LH- inhibition effect. The pre -incubated LH-ha,rrrrone with FDE of M.officinalis in phosphate buffer pH 7.5 also showed a clear antihormonal effect, while the treatments of 20Yo oxidized FDE of Mel. officinalis showed relatively lesser effect than the above two mentioned treatments.. The most inhibition phase was associated with 20% oxidized Mel. officinalis (FDE) preincubated in phosphate buffer pH7.S.Oxidation of caffeic acid by the polyphenol oxidase, which has been isolated from Melissia and purified by ion exchange chrornatography ,also leads to the formation of oligomers which exert also the LH inhibition to the same extent as the last mentioned treatrnent.So the addition of 25 pg of (20% oxidized M. officinalis ,preincubated in phosphate buffer) and the product formed by enzyrne action,brought the LH inhibtion to zero.
Keywords: Melissia officinaiis; antileutinizing cornpound; polyphenols